Occult hepatitis C virus infection among Egyptian hemodialysis patients and its potential effect on anemia management - Mostafa Abdelsalam; Mona M Tawfik; Alaa Habib; Ahmed Abdel-Razik; Nahla Anber; Maysaa Zaki; Mohammad S Marie (SpringerOpen, 2019)
Background Hepatitis C virus (HCV) infection is still a main health problem in hemodialysis (HD) patients. The prevalence of occult hepatitis C infection (OCI) in HD patients may be underestimated, and its possible influence on anemia management has not been studied. We aimed to determine the existence of OCI in Egyptian HD patients as well as its possible effect on anemia management. Patients and methods This cross-sectional multicenter study included 98 HCV-negative HD patients (negative for both anti-HCV antibody and HCV-RNA), 43 anti-HCV-positive HD patients, and 10 volunteer people matched for age and sex as a healthy control group. Serology test for anti-HCV antibody, reverse-transcription PCR for HCV-RNA (both serum and peripheral mononuclear cell (PMNC)), complete blood count (CBC), liver transaminases, serum iron, serum ferritin, and high-sensitivity C-reactive protein (hsCRP) were done. The average erythropoiesis-stimulating agent (ESA) doses were calculated over 6 months, and ESA resistance index was calculated. The frequency of packed red blood corpuscle (RBC) transfusion for each patient was recorded. Results Our HD patients had significant higher levels of serum ferritin (P=0.011), higher serum alanine aminotransferase and aspartate aminotransferase (P=0.002 and 0.006, respectively), higher hsCRP (P<0.0001), and significant lower level of hemoglobin (P<0.0001) compared with the healthy control group. The prevalence of OCI was 8.16% (8 of 98 patients). OCI patients had significant longer dialysis duration, higher transaminases, higher hsCRP, higher serum ferritin, and higher frequency of packed RBCs transfusion (P<0.0001), whereas mean hemoglobin levels and ESA resistance index showed insignificant differences compared with HCV-negative HD patients. Using logistic regression analysis, frequency of packed RBC transfusion and aspartate aminotransferase were the only independent predictors for OCI (P=0.012 and 0.049, respectively), and by multivariate analysis, no significant predictors were found to be associated with anemia in patients with OCI. Conclusion The prevalence of OCI in our study was 8.16%. OCI had no effect on anemia managements.